2017
DOI: 10.4236/ojn.2017.76049
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Occupational Stress among Emergency Nurses at Private Hospitals in Bangkok, Thailand

Abstract: Introduction: Occupational stress has negative effects on employee's health and organizational productivity. Nurses in emergency department are more exposed to stress than nurses in other departments. Aim: To explore nurses' experiences of occupational stress in emergency departments in private hospitals in Bangkok, Thailand. Design: A descriptive qualitative design, with a deductive approach based on the Job Demand-Control-Support model was used. Methods: Fifteen emergency department nurses at two different h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
1
21
1
3
Order By: Relevance
“…reached quite similar results and stated that there was no relationship between work experience and occupational stress among emergency medical technicians, but in work experience of more than 20 years, the sum of scores of stressors was higher [14]. Yuwanich et al [15] stated that low experience and work experience are related to occupational stress of nurses in emergency medical services and Bardhan et al similarly indicated that work experience less than 10 years is a strong risk factor of higher occupational stress in nurses, which is somewhat consistent with the present study [27]. On the other hand, d'Ettorre et al considered work experience related to occupational stress in burses of emergency medical services [8].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…reached quite similar results and stated that there was no relationship between work experience and occupational stress among emergency medical technicians, but in work experience of more than 20 years, the sum of scores of stressors was higher [14]. Yuwanich et al [15] stated that low experience and work experience are related to occupational stress of nurses in emergency medical services and Bardhan et al similarly indicated that work experience less than 10 years is a strong risk factor of higher occupational stress in nurses, which is somewhat consistent with the present study [27]. On the other hand, d'Ettorre et al considered work experience related to occupational stress in burses of emergency medical services [8].…”
Section: Resultsmentioning
confidence: 88%
“…In other words, the physical, mental, and intellectual stressors cause the emergency medical technicians to be exposed at high risk, such as accidents, errors, and other injuries to persons (6). The clear examples of symptoms of occupational stress include insomnia, distraction, anxiety, absenteeism, depression, fatigue, excessive frustration, family problems, and physical problems such as heart disease, migraines, headaches, indigestion, and disc herniation between the lumbar vertebrae [15]. Increasing working hours causes the increase of conflict in occupational and family tasks which can lead to occupational stress [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedimento para coletar a saliva com o tubo Salivette: (LU et al, 2015;PRADO, 2016;YUWANICH et al, 2017;ÇELIK et al, 2017;SALVAGIONI et al, 2017;NICOLAIDES et al, 2017;AKBAR et al, 2017). Silveira et al (2009) SOUZA et al, 2009;SILVEIRA et al, 2009;KLEINUBING et al, 2013 LOPES, 2008;URBANETTO et al, 2011;SALVAGIONI et al, 2017;NICOLAIDES et al, 2017).…”
Section: Critérios De Exclusãounclassified
“…Silveira et al (2009) SOUZA et al, 2009;SILVEIRA et al, 2009;KLEINUBING et al, 2013 LOPES, 2008;URBANETTO et al, 2011;SALVAGIONI et al, 2017;NICOLAIDES et al, 2017). Esses dados da literatura, bem como os encontrados neste estudo, evidenciam que pouco vem sendo feito para sanar ou minimizar o surgimento do estresse entre profissionais de enfermagem, uma vez que estudos atuais (LU et al, 2015;PRADO, 2016;YUWANICH et al, 2017;ÇELIK et al, 2017;SALVAGIONI et al, 2017;NICOLAIDES et al, 2017;AKBAR et al, 2017) apresentam resultados semelhante aos obtidos há mais de 10 anos (KAGEYAMA et al, 2001;PAFARO;MARTINO, 2004;BATISTA;BIANCHI, 2006).…”
Section: Critérios De Exclusãounclassified